Kampung Edukasi: Development of an Educultural Tourism-Based Village in Boyolali - Triyono, Agus; Shahrani Widaryanto, Assyifa (Jogjakarta Communication Conference (JCC), 2025)
Community empowerment is defined as efforts to make communities more empowered and self-reliant. The form of community empowerment itself must be adapted to the various potentials, problems, and needs of the community. Kampung Edukasi in Kembangkuning Village, Boyolali Regency, is an educultural tourism-based village managed independently by the community. The objective of this research is to examine how community empowerment is carried out by the residents of Kembangkuning Village in developing Kampung Edukasi. The research method used in this study is qualitative descriptive, with data collection conducted through interviews, observation, and documentation. The informant selection technique employed snowball sampling, with the key informant being Uun Sismiyardi, the Bayan (village official) of Dukuh Duren Sari. The results of this study indicate that three out of the five elements of Empowerment proposed by Edi Soeharto are functioning well, including the indicators of enabling, strengthening, and sustaining. Meanwhile, the indicators of protection and support are less optimal due to the still high involvement of external parties.